A Case Study to Determine Drivers and Barriers of Appalachian Forest Products in Central America - Lyon, Scott W. (2012)
The purpose of this research was to determine drivers and barriers of Appalachian wood product competitors in Central America. Potential market opportunities for Appalachian forest product companies in Central America were evaluated and strategies were developed to increase exports of Appalachian wood products to Central America. The findings support the claim that United States forest product companies have not put enough effort into marketing forest products to Central America. Forests in El Salvador, Panama, and Costa Rica are limiting harvests and the industry lacks support from the government, reducing the amount of raw material and production. Inconsistencies between Appalachian and Central American wood products industries (e.g., dimensions) act as a barrier to the efficient exchange of wood products. The best market strategies for Appalachian forest products companies to increase sales into Central America are: partner with local wholesalers, offer higher value-added products, and maintain similar pricing with competition. An outside source of wood is needed to meet the needs of growing regional infrastructure.